Monitoring wildlife-vehicle collisions: analysis and cost-benefit of escape ramps for deer and elk on U.S. Highway 550 - Siemers, Jeremy L., author; Wilson, Kenneth R., author; Baruch-Mordo, Sharon, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2015)
Wildlife fencing along highways can lower wildlife-vehicle collision rates by excluding animals from the road right-of-way. Still, animals can breach fencing and end up trapped within the fencing along the highway right-of-way, exposing wildlife and motorists to the risk of collision. Wildlife escape ramps are designed to allow trapped animals safe passage out of the right-of-way. Few recommendations exist on effective design of escape ramps and monitoring data are limited. We investigated the usage levels, escape success, wildlife-vehicle collisions, and design of 11 escape ramps and two escape jumps along an eight-mile stretch of U.S. Highway 550 near Ridgway, Colorado. Our goals were to 1) relate usage levels and escape success to ER structure design and its surrounding environmental characteristics, 2) describe the animal use of ER in the study area, 3) conduct a cost-benefit analysis for escape ramp construction and 4) provide recommendations regarding ER design and WVC based on data collected.
Prepared for: Colorado Department of Transportation, Division of Transportation Development, Applied Research and Innovation Branch. Prepared in cooperation with the US Department of Transportation, Federal Highway Administration.
Report No. CDOT-2015-5.
May 2015.